Human Trafficking: A Bibliometric Analysis Using Scopus Database: Examining the Research Landscape and Trends in Human Trafficking (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Trafficking of human beings is a humane crime. It also represents a severe danger to world safety and health. Globalization has made it simpler for criminal groups to deal with people trafficking. No volume statistics, research trends and significant players in this discipline are provided. The objective of this study was thus to evaluate the research activities and trends in trafficking in human beings.There has been a bibliometric technique. Literature published in Scopus database indexed academic journals has been found. The research period was established between 2000 and 2017.There were found two thousand 44 papers. Per document the average number of authors was 1.9. Over one-third of the data retrieved (n=771 37.7 percent) pertain to sex trade, 616 (30.1 percent ) to labour traffickingforced labour, 199 (9.7 percent ) to minors, and 138 (6.8 percent ) to organ trafficking. In health sectors, one third (n = 707 34.6 per cent), but in social sciences and humanities, the number was 1526 (74.7 per cent) (74.7 per cent). In the US, the number of papers published was positioned first (n = 735 36.0 percent). The geographic distribution of the document recovered revealed that the least research contribution was made to globe regions with a high frequency. There is limited contribution to the retrieved literature from multinational scientific efforts. The most active institution was Harvard University (USA), which is n=39, 1,9 percent . The most active journal for publishing HT content was International Migration (n = 35 1.7 percent). The most citations per document have been achieved in articles published in the transplantation journal (25.5) and two of the most regularly mentioned publications linked to organ commerce.